2021
DOI: 10.1002/ecs2.3527
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a common antidepressant alters crayfish behavior and has potential subsequent ecosystem impacts

Abstract: Pharmaceuticals are ubiquitous in aquatic environments, yet little is known regarding their impacts on ecological processes. Selective serotonin reuptake inhibitors (SSRIs) are frequently prescribed human antidepressants and have been shown to alter crayfish behavior. These behavioral alterations are particularly relevant as crayfish play a central role in freshwater ecosystems and often reach high biomass in anthropogenically influenced environments commonly exposed to pharmaceutical contamination. Using a 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…The discharge of effluents from wastewater treatment plants (WWTPs) into surrounding waterways can have detrimental effects on the health of aquatic ecosystems. For one, WWTPs discharge important pollutants, including pharmaceuticals 1 , 2 and household products 3 , which can impact on the local fauna 4 as well as microbial communities 5 , 6 . WWTP can also be a source of allochthonous microorganisms distinct from the receiving waterway, including pathogens 7 and antibiotic-resistant bacteria 8 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The discharge of effluents from wastewater treatment plants (WWTPs) into surrounding waterways can have detrimental effects on the health of aquatic ecosystems. For one, WWTPs discharge important pollutants, including pharmaceuticals 1 , 2 and household products 3 , which can impact on the local fauna 4 as well as microbial communities 5 , 6 . WWTP can also be a source of allochthonous microorganisms distinct from the receiving waterway, including pathogens 7 and antibiotic-resistant bacteria 8 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Brodin et al (2013) reported that European perch ( Perca fluviatilis ) exposed to oxazepam, a type of benzodiazepine, at environmentally relevant concentrations were less social and bolder than unexposed individuals. It was also reported that spinycheek crayfish ( Faxonius limosus ) exposed to citalopram, a type of antidepressant, at an environmentally relevant concentration showed increased boldness (Reisinger et al, 2021). As these studies have shown, and as Bertram et al (2022) reviewed, the behavior of organisms can be remarkably sensitive to pollutants at even low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the previously introduced tricyclic antidepressants, CTL offers advantages owing to its therapeutic profile, superior acceptability, and safety, which justifies its popularity in the treatment of major depressive disorders [ 3 , 15 , 16 ]. In parallel, there is limited information on its environmental fate and toxicity, raising concerns regarding the potential effects on exposed wildlife [ 17 , 18 , 19 ]. Therefore, the monitoring of its presence in environmental compartments is imperative.…”
Section: Introductionmentioning
confidence: 99%